Media dalam Perspektif Masyarakat Tontonan Jokowi Spectacle - Ragil Putri, Sukma Ari (Universitas Semarang, 2015)
In this era, celebrities are shaped and disseminated by the media. Media generates celebrities. When someone become the most popular person in the news then he/she would instantly become a celebrity. One of the figures that always make an interesting spectacle is Jokowi. As a presidential candidate of PDI Perjuangan, Jokowi have all aspects to be an interesting spectacle because of his construction of self-image that is different from the self-image of other president in Indonesia. As a media darling, Jokowi makes a Jokowi Spectacle. It becomes much more interesting when Jokowi Spectacle is compared with its successor, Obama Spectacle.